PERBEDAAN KECEMASAN CEDERA BERULANG BERDASARKAN STRATEGI COPING STRES PADA ATLET YANG PERNAH CEDERA - Sonia Marcellina; Herdiyan Maulana (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
Abstract This study was conducted to determine significant re-injury anxiety difference based on coping stress strategies among injured athletes. The sample used in this study amounted to 76 athletes. Sampling technique using simple random sampling at the Student Education and Training Centre at Ragunan. Hypothesis that proposed in this research was there is significant re-injury anxiety difference based on coping stress strategies among injured athletes. Hypothesis testing using independent sample t-test. Significance value of t-test is lower than the value of t table. So the results of the study concluded that there is no significant re-injury anxiety difference based on coping stress strategies among injured athletes. Keywords :. Loneliness, tendency of self injury behavior, inmates